Structure-function specialisation of the interfascicular matrix in the human achilles tendon. (1st September 2021) - Patel, Dharmesh; Zamboulis, Danae E.; Spiesz, Ewa M.; Birch, Helen L.; Clegg, Peter D.; Thorpe, Chavaunne T.; Screen, Hazel R.C.
Abstract: Tendon consists of highly aligned collagen-rich fascicles surrounded by interfascicular matrix (IFM). Some tendons act as energy stores to improve locomotion efficiency, but such tendons commonly obtain debilitating injuries. In equine tendons, energy storing is achieved primarily through specialisation of the IFM. However, no studies have investigated IFM structure-function specialisation in human tendons. Here, we compare the human positional anterior tibial tendon and energy storing Achilles tendons, testing the hypothesis that the Achilles tendon IFM has specialised composition and mechanical properties, which are lost with ageing. Data demonstrate IFM specialisation in the energy storing Achilles, with greater elasticity and fatigue resistance than in the positional anterior tibial tendon. With ageing, alterations occur predominantly to the proteome of the Achilles IFM, which are likely responsible for the observed trends towards decreased fatigue resistance. Knowledge of these key energy storing specialisations and their changes with ageing offers crucial insight towards developing treatments for tendinopathy. Statement of significance: Developing effective therapeutics or preventative measures for tendon injury necessitates the understanding of healthy tendon function and mechanics. By establishing structure-function relationships in human tendon and determining how these are affected by ageing, potential targets for therapeutics can be identified. In this study, we have used a combination of mechanical testing, immunolabelling and proteomics analysis to study structure-function specialisations in human tendon. We demonstrate that the interfascicular matrix is specialised for energy storing in the Achilles tendon, and that its proteome is altered with ageing, which is likely responsible for the observed trends towards decreased fatigue resistance. Knowledge of these key energy storing specialisations and their changes with ageing offers crucial insight towards developing treatments and preventative approaches for tendinopathy. Graphical abstract: Image, graphical abstract